Robotic process automation in secure supply chain management - Cheang, Kit Yann (2024)
This project is a development-based project with automation for academic purposes. The integration aims to enable organizations to automate security assessments and enhance overall supply chain security. Given that RPA is a relatively new technology, this thesis includes a systematic literature review of similar platforms and technologies available in the market. Current development challenges include financial constraints, security risks, privacy concerns, and complexities in integrating RPA with SCM. Various blockchain platforms and smart contracts are reviewed, with a focus on designing and integrating blockchain technology into SCM processes. The reviewed blockchain platforms include Ethereum, Hyperledger Fabric, Quorum, and Corda. Besides, it explores the application of blockchain in SCM, emphasizing its potential to enhance transparency and efficiency. Furthermore, it reviews several companies IBM Food Trust, Provenance, Walmart, and TradeWaltz that have successfully incorporated blockchain technology into their supply chain operations, showcasing real-world benefits and implementations. This project details the system design, focusing on Hyperledger Fabric’s transaction workflow and the supply chain architecture, along with the Hyperledger Firefly development stack. Last of all, the expected outcome of this project is to integrate RPA and blockchain technology into supply chain management to improve security and overall efficiency. Keywords: Robotic Process Automation, Supply Chain Security, Blockchain Integration, Hyperledger Firefly, Smart Contract Technology, Automation in SCM, Blockchain Platforms, Security Assessments, SCM Transparency, Blockchain Implementation, Hyperledger Fabric Workflow, SCM Efficiency, Real-World Blockchain Applications, Blockchain for Security, RPA in Supply Chain Management